Knowledge and practices of operating room nurses in the prevention of pressure injuries. Issue 1 (February 2022) - Cebeci, Fatma; Şenol Çelik, Sevilay
Abstract: Background: Operating room (OR) nurses play an important role in preventing the pressure injuries (PIs) that may develop during the perioperative process. This study was conducted to determine OR nurses' level of knowledge about PIs, and how they manage them. Methods: This is a cross-sectional, quantitative and descriptive study. The sample of the study consisted of 234 OR nurses working in eight different public hospitals in Ankara. The questionnaire applied in this study was prepared in accordance with the guidelines. This questionnaire consisted of three sections: demographic profiling, common preventive practices, and the knowledge of OR nurses about intraoperative PI prevention. Findings: 66.7% of the participants had received education about PIs during their basic nursing training, and 41.5% had received education after graduation. 97.4% of OR nurses did not follow international guidelines about PIs. The mean total score of the OR nurses for the questions about PIs was 52.0 ± 13.7 out of a possible score of 100. The lowest mean score was obtained for the topic of 'staging pressure injuries', and the highest score was obtained from 'interventions to prevent pressure injuries'. In addition, 81.5% of the OR nurses stated that they were not given information about patients with a high PI risk by clinical nurses. 97.9% of the OR nurses did not use a scale to assess intraoperative PI risks. Fewer than half of the nurses said that they assessed the risk of PIs during surgery. 90.8% the nurses did not record risk assessment and interventions to prevent PIs. Conclusion: There is a need to incorporate basic operating room PI (ORPI) training into both the basic nursing and in-service training to improve the knowledge of OR nurses about how to prevent and manage ORPIs. In addition, measures to assess PI risk and prevent ORPI should be included in institutional policies and procedures. Highlights: OR nurses working at eight hospitals had generally low scores with regard to their knowledge of PI prevention and management. 97.4% of OR nurses did not follow the guidelines regarding PI, and 97.9% did not use a scale to assess their patients' risk. 81.5% of the OR nurses claimed that they were not given information about patients with a high PI risk by clinical nurses. The measures taken by OR nurses to prevent ORPI are inadequate.